Study on influence of propellant flow rate on ECR ion source beam current - MOU, Hao; GENG, Hai; WU, Xianming; PU, Yanxu; TAN, Renwei; YANG, Juan (Xibei Gongye Daxue Xuebao, 2024)
The electron cyclotron resonance (ECR) ion source with grid inlet has the characteristics of low propellant supply pressure and no cathode required for operation, so it has the potential for application in atmosphere breathing electric propulsion. The flow rate has a significant impact on the beam current of the ion source. When the flow rate exceeds the critical flow rate, the increase of the ion beam is suppressed. To clarify the determining factors that limit the increase of ion beam flow, this paper conducted Langmuir probe diagnostic experiments on ECR ion sources with grid inlet driven by nitrogen gas at different flow rates, and calculated the distribution of ordinary (O) wave cutoff region and electron energy acquisition indicators based on the diagnostic results. The research results indicate that when the flow rate is below the critical flow rate, the ion density rapidly increases with the increase of flow rate, and the main factor limiting the increase of ion beam is the neutral gas density. When the flow rate exceeds the critical flow rate, the O wave cutoff zone almost covers the entire main plasma production aera, which leads to a decrease of one order of magnitude in the efficiency of electron energy acquisition. At this moment, the main factor limiting the increase of ion beams shifts to electron temperature. 栅格进气道电子回旋共振(electron cyclotron resonance, ECR)离子源推进剂供给压强低、无阴极, 有应用于吸气式电推进系统的潜力。流量对离子源的束流影响显著, 当流量超过临界流量时, 离子束流的增长受到抑制。为明晰限制离子束流增长的根本原因, 开展不同流量下氮工质栅格进气道ECR离子源的Langmuir探针诊断实验, 并基于诊断结果计算了寻常(ordinary, O)波截止区和电子获能指标的分布。研究结果表明, 当流量低于临界流量时, 随着流量增加, 离子密度快速增加, 限制离子束流增长的主要因素是中性气体密度。当流量超出临界流量时, O波截止区几乎覆盖整个等离子体产生区域, 这导致电子能量获取效率下降了一个数量级。此时, 限制离子束流增长的主要因素转变为电子温度。